Left atrial strain by speckle tracking predicts atrial fibrosis in patients undergoing heart transplantation. (12th June 2021) - Lisi, Matteo; Mandoli, Giulia Elena; Cameli, Matteo; Pastore, Maria Concetta; Righini, Francesca Maria; Benfari, Giovanni; Rubboli, Andrea; D'Ascenzi, Flavio; Focardi, Marta; Tsioulpas, Charilaos; Bernazzali, Sonia; Maccherini, Massimo; et al.
Abstract: Aims: In patients with heart failure (HF), chronically raised left ventricular (LV) filling pressures lead to progressive left atrial (LA) dysfunction and fibrosis. We aimed to assess the correlation of LA reservoir strain (peak atrial longitudinal strain, PALS) by speckle tracking echocardiography (STE) and LA fibrosis assessed by myocardial biopsy in patients undergoing heart transplantation (HTx). Methods and results: Forty-eight patients with advanced HF [mean age 51.2 ± 8.1 years, 29% females; LV ejection fraction ≤25% and New York Heart Association (NYHA) class III–IV] referred for HTx were enrolled and underwent pre-operative echocardiographic evaluation, right heart catheterization, and cardiopulmonary exercise testing. Exclusion criteria were non-sinus rhythm, mechanical ventilation, severe mitral/tricuspid regurgitation, or other valvular disease and poor acoustic window. After HTx, LA bioptic samples were collected and analysed to determine the extent of myocardial fibrosis (%). LA fibrosis showed correlation with PALS ( R = −0.88, P < 0.0001), VO2 max ( R = −0.68, P < 0.0001), NYHA class ( R = 0.66, P < 0.0001), LA stiffness ( R = 0.58, P = 0.0002), and E / e ' ( R = 0.44, P = 0.005), while poorly correlated with E / A ratio ( R = 0.23, P = 0.21). PALS had a good correlation with NYHA class ( R = −0.64, P < 0.0001), PAoP ( R = −0.61, P = 0.03) and VO2 max ( R = 0.57, P = 0.0001). Multivariate regression analysis identified PALS (beta = −0.91, P < 0.001) and LA Volume (beta = −0.19, P = 0.03) as predictors of LA Fibrosis, while E / e ' was not a significant predictor (beta = 0.15, P = 0.08). Conclusion: Emerging as a possible index of myocardial fibrosis in patients with advanced HF, PALS could help to optimize the management and the selection of those patients with irreversible LA structural damage for advanced therapeutic strategies.